Preditores locais e de paisagem da herbivoria em cultivos de milho e feijão na Caatinga - Silva, Ivânia Clea Santos de França (2022)
The Earth’s land surface occupied by agricultural fields are predicted to expand by up 30% until 2050. Despite the relevance of crop production to ensure food safety to the world growing population, land-use changes generated by ‘modern’ agricultural activities have driven speciesrich ecosystems towards collapse, implying on the necessity of developing sustainable agroecosystems in which ecosystems services are harnessed. Here, we aimed to assess which and how local and landscape variables impact the ecosystem service of herbivory level control. We analyzed, in nine properties in the Cariri Paraibano, how local and landscape structure influence herbivory levels in maize and bean crops. Landscape structure was defined through metrics of composition, configuration, land use diversity and the distance to large, forested areas, in three different scales (100m, 300m and 500m radius). Herbivory levels (frequency and magnitude of the damage) were estimated with the aid of a ruler and by observing the presence or absence of damage on plant structures (i.e. leaves and fruits). Our results demonstrated that as local structure, the structure of the landscape surrounding agricultural fields must be considered in the design of sustainable agricultural landscapes.